2020
DOI: 10.3389/fphar.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Chinese Herbal Products Therapy Reduces the Risk of Ischemic Stroke Among Patients With Rheumatoid Arthritis

Abstract: We performed a retrospective cohort study to investigate the association between the risk of ischemic stroke (IS) and the use of Chinese herbal products (CHP) in combination with western medicine (WM) among patients with rheumatoid arthritis (RA). The data were sourced from the registry for beneficiaries, inpatient and ambulatory care claims, and Registry for Catastrophic Illness from the National Health Insurance Research Database (NHIRD) in Taiwan between 1997 and 2011. Patients, who were newly diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Recently, a retrospective cohort study also indicated that adding GSZD was associated with a lower risk of ischemic stroke among patients with RA. 42 Thus, these results suggest that the combination of GSZD and MTX may be safer than MTX alone for RA patients, especially for patients with MTX related gastrointestinal AEs. Further studies are needed to confirm whether adding GSZD was associated with a lower rate of total AEs.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, a retrospective cohort study also indicated that adding GSZD was associated with a lower risk of ischemic stroke among patients with RA. 42 Thus, these results suggest that the combination of GSZD and MTX may be safer than MTX alone for RA patients, especially for patients with MTX related gastrointestinal AEs. Further studies are needed to confirm whether adding GSZD was associated with a lower rate of total AEs.…”
Section: Discussionmentioning
confidence: 75%
“…East Asian herbal medicine (EAHM) could be a useful candidate for RA treatment that meets aforementioned objective. In East Asian nations such as China, Korea, and Japan, 500 to 1000 EAHM materials are commonly listed in pharmacopeia and are still actively utilized as medications for the treatment of rheumatic and musculoskeletal illnesses such [10–13] …”
Section: Introductionmentioning
confidence: 99%
“…In East Asian nations such as China, Korea, and Japan, 500 to 1000 EAHM materials are commonly listed in pharmacopeia and are still actively utilized as medications for the treatment of rheumatic and musculoskeletal illnesses such. [10][11][12][13] Based on previous study knowledge and challenge awareness, the authors set the following research objectives:…”
Section: Introductionmentioning
confidence: 99%